STRATEGI PEMASARAN SYARIAH DALAM MENINGKATKAN PENJUALAN DI TOKO ASHFINA SHOP BLOKAGUNG KECAMATAN TEGALSARI KABUPATEN BANYUWANGI - Eka Septiarani; Sofi Faiqotul Hikmah (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to describe the implementation of sharia marketing in the Blokagung Ashfina Shop, sharia review of sharia marketing in the Ashfina Shop store, and the influence of sharia marketing in increasing Ashfina Shop shop sales. This type of research is a qualitative method with descriptive studies. Data collection techniques carried out by observation, interviews, and documentation. Based on the results of the research, the sharia marketing strategy undertaken by the Ashfina Shop is to improve services to consumers, goods sold are increasingly equipped and reproduced, prices of goods sold are cheap, strategic locations/ locations, word of mouth promotion. The sharia marketing strategy adopted by the Ashfina Shop stores is very influential in increasing sales. This is evidenced by the increasing number of consumers who come to the Ashfina Shop.